Acid Mine Drainage Remediation By A Combined Chemical/Biological Treatment I - Chemical Pre-Treatment - M. Di Tommaso (Society for Mining, Metallurgy & Exploration, 2006)
Acid Mine Drainage (AMD) is a quite diffuse environmental problem in dismissed sulphur mine districts. AMD is related to sulphur oxidation of abandoned tailings, generating heavy metal-bearing streams with high iron and sulphate contents and low pH. Treatments of AMD aim firstly to increase the pH to reduce its leaching power causing the further release and mobilization of heavy metals through soil solution and groundwaters. Increasing the pH also allows the precipitation of iron (III) (involved in sulphur oxidation and then in AMD generation) and the partial removal of other toxic components such as arsenic. pH adjustment and the reduction of the high concentration of iron are also necessary for the successive biological treatment in permeable reactive barriers (PRB) with sulphate reducing bacteria (SRB) (II step, biologically mediated precipitaton/biosorption) to avoid the rapid plugging of the barrier (for the large amounts of iron precipitates) and to ensure neutral pH conditions for SRB growth. In this work the first step (chemical precipitation) of a combined chemical and biological treatment of AMD is presented. Experimental data from column tests using carbonate stones to remove iron and increase pH were reported. Toxicity tests have been carried out on the treated wastewaters by Lepidium sativum.